Nicardipine Inhibits Breast Cancer Migration via Nrf2/HO-1 Axis and Matrix Metalloproteinase-9 Regulation - Chen, Yen-Chang; Chen, Jia-Hong; Tsai, Cheng-Fang; Wu, Chen-Teng; Wu, Miao-Hsiang; Chang, Pei-Chun; Yeh, Wei-Lan (Frontiers in Pharmacology, 2021)
Background Metastasis represents an advanced stage of cancers, and matrix metalloproteinases are critical regulators. Calcium signal is crucial for appropriate cell behaviors. The efficacy and effects of calcium channel blockers in treating cancers are individually differ from each other. Here, we attempt to investigate the effects of nicardipine, a FDA-approved calcium channel blocker, in advanced breast cancers. Methods We analyzed the influence of nicardipine on the colony-forming ability of triple negative breast cancer cell lines. Using cell culture inserts, cell migration was also examined. The expression of regulatory proteins were evaluated by real time-PCR, Western blot, and ELISA. Results We have confirmed that nicardipine inhibits breast cancer cells migration and colony formation. In addition, we also revealed that nicardipine increases Nrf2 and HO-1 expression. Inhibition of HO-1 abrogates nicardipine-reduced matrix metalloproteinase-9 expression. Moreover, the end products of HO-1, namely, CO, Fe2+, biliverdin (will converted to bilirubin), also decreases the expression of matrix metalloproteinase-9. Conclusion These findings suggest that nicardipine-mediated matrix metalloproteinase-9 reduction is regulated by Nrf2/HO-1 axis and its catalytic end products. Therefore, nicardipine may be a potential candidate for re-purposing against advanced breast cancers.